(untitled) (Research, Society and Development, 2021)
The objective of this work was to survey the didactic resources produced to assist in the teaching-learning process of botanical contents for basic education in Brazil. Thus, an integrated literature review was carried out with meta-analysis through the Google Scholar platform, using the following descriptors: “botany teaching”, “didactic resource” and “basic education”, from 2000 to May 2021. Content analysis was used to express nuances of the content, categorizing the features found based on similarities. in general, it was identified that there has been an increase over the years in didactic production for the teaching of botany, especially concentrated in the Brazilian Northeast. In total, there were 59 resources, distributed into six categories (audiovisual, game, plant material, didactic model, textual-visual and technological), which had their main didactic information such as name, type, objective, content, modality, limitations and results obtained described in an integrative way to facilitate the access of teachers to possible resources to be used in their pedagogical practice. In this way, the survey, description, and integration of didactic resources directed to the teaching of botany, presented here, can facilitate the access and choice of professors of the resource that best fits or is closer to their reality and pedagogical practice in classes on botanical content, from the knowledge of the didactic information of these productions. This can favor an increase in the frequency of use of these pedagogical productions in the classroom.